A97 HLA-DQA1-HLA-DRB1 POLYMORPHISM IS A MAJOR PREDICTOR OF AZATHIOPRINE-INDUCED PANCREATITIS IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (1st March 2018) - Wilson, A; Jansen, L; Rose, R; Gregor, J C; Ponich, T; Chande, N; Khanna, R; Yan, B; Jairath, V; Khanna, N; Sey, M; Beaton, M D; et al.
Abstract: Background: Azathioprine (AZA)-induced pancreatitis is an unpredictable and dose-independent adverse event affecting 2–7% of patients with inflammatory bowel disease (IBD) patients treated with AZA. There are no tools in clinical practice to identify at-risk individuals; however, a genome wide association study (GWAS) identified a strong association between the Class II HLA gene region polymorphism (rs2647087) and AZA-induced pancreatitis. Aims: To independently confirm the findings of the GWAS in an IBD cohort, to evaluate its utility in clinical practice and to offer a novel AZA treatment algorithm for IBD based on pharmacogenomic principles. Methods: A retrospective cohort study evaluated 373 AZA-exposed IBD patients from a tertiary care academic centre in London, Canada. All subjects underwent screening for the single nucleotide polymorphism (SNP) rs2647087 mapped to the HLA-DQA1*02:01-HLA-DRB1*07:01 haplotype and were sub-divided based on the presence (n = 13) or absence (n = 360) of an AZA-induced pancreatitis diagnosis. The risk of AZA-induced pancreatitis was assessed based on rs2647087 genotype. Results: The risk of pancreatitis during AZA-therapy was highly predictable and genotype dependent: 0.53% for wild-type (A/A), 4.25% (OR=4.19, 95%CI 1.02–36.45, p=0.044) for heterozygous (A/C), and 14.63% (OR=15.83, 95%CI 3.80–145.26, p=0.0001) for homozygous variant (C/C) patients. Conclusions: The class II HLA region (at rs2647087) is an important marker of AZA-induced pancreatitis risk. We propose a simple and clinically implementable algorithm based on rs2647087 and TPMT genotypes for AZA selection and dosing for patients with IBD. Funding Agencies: CAG, CCC, CIHRCancer Care Ontario